Impact of capital regulation and market discipline on capital ratio selection: A cross country study - Ahmed Imran Hunjra; Qasim Zureigat; Rashid Mehmood (International Journal of Financial Studies, 2020)
We aim to analyze the impact of capital regulation and market discipline on capital to risk-weighted assets ratio. We used the panel data of Asian developing-countries banks for the period from 2009 to 2018. We collected data from the financial statements of 73 banks of Pakistan, Jordan, Indonesia, the Philippines, Saudi Arabia, and Thailand. We used the generalized method of moment (GMM) to analyze the results. We find that capital regulation and market disciplines significantly influence the capital ratio in Asian developing countries.
Keywords: G21; G32; 330; capital ratios and financial institutions; capital regulation; market discipline